2021
DOI: 10.1371/journal.pone.0256594
|View full text |Cite
|
Sign up to set email alerts
|

Uricase deficiency causes mild and multiple organ injuries in rats

Abstract: Uricase-deficient rats could be one of the optimal model animals to study hyperuricemia. The present study aimed to find the biological differences between uricase-deficient (Kunming-DY rats) and wild-type male rats. Uricase-deficient rats and wild-type rats were commonly bred. Their body weight, water and food consumption, 24-h urine and feces, uric acid in serum and organs, and serum indexes were recorded or assayed. Organs, including the heart, liver, spleen, lung, kidney, thymus, stomach, duodenum, and ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…It has been reported that uricase deficiency causes multiple mild organ injuries in KDY rats ( Fan et al, 2021 ), which was further verified in the present study. The possible mechanisms underlying these injuries may be associated with Uox, the protein of uricase, or the elevation of SUA, which requires further investigation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been reported that uricase deficiency causes multiple mild organ injuries in KDY rats ( Fan et al, 2021 ), which was further verified in the present study. The possible mechanisms underlying these injuries may be associated with Uox, the protein of uricase, or the elevation of SUA, which requires further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…Uricase deficiency caused multiple mild organ injuries in KDY rats ( Fan et al, 2021 ), similar to the phenomena observed in uricase-deficient mice ( Guo et al, 2019 ). In the control group, swollen hepatic cells were observed, and the sinuses were crowded with swollen hepatic cells, which caused the hepatic sinuses to be very narrow ( Fig.…”
Section: Resultssupporting
confidence: 59%
“…As reported previously [ 17 , 24 ], Uox -/- rats are apparently healthy. Their serum creatinine and urea are at low levels in the normal ranges, although they are significantly higher than those in wild-type rats.…”
Section: Discussionsupporting
confidence: 82%
“…Considering the mass of the organs, the total uric acid in an organ was calculated by multiplying the uric acid content by its weight [ 24 ]. According to the results shown in Fig 6D , the liver, small intestine, and kidneys were the top three organs in uric acid distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation